PHARMACOLOGICAL EVALUATION OF NOVEL COMPOUNDS AS ALZHEIMER’S DISEASE TREATMENT - Li, Tian-Tian (2024)
Background: Alzheimer’s Disease (AD) is an age-related and progressive neurogenerative disorder characterised by a progressive loss of memory and cognitive impairments. Excessive Aβ deposition and tau hyperphosphorylation are pathological characteristics of AD, which are accompanied by oxidative stress, metal dysregulation, and neuroinflammatory processes. Currently, most medications being tested in clinical trials for AD are anti-amyloid therapies. Nevertheless, given the ineffectiveness of small-molecule medicines targeting Aβ, there has been a shift in the emphasis of drug research towards the creation of medications that target alternative pathways, such as anti-tau, anti-inflammatory, and multi-target therapies. The development of multi-target medications has the benefit of compensating for the inadequacy of modulating a single target to achieve the desired disease-modifying effectiveness in complex, multifactorial disorders like AD. Additionally, neuroinflammation, which is central to AD's pathology, results in synaptic and neuronal damage. Cannabis-derived cannabidiol (CBD) has been shown to be a promising AD drug because it has anti-inflammatory, antioxidant, and neuroprotective properties. CBD has been shown to inhibit the formation and aggregation of tau fibrils and protect against microglial and Aβ-induced neurotoxicity.